Kundalini yoga: práticas de liberdade em contextos de aprisionamento - Davi Pantuzza Marques (2017)
The experience of self-seeking is part of human nature. Throughout human history, theories, practices, manners and lifestyles have been invented by human beings so that they can find meaning in their lives. In this sense, this research seeks to relate two seemingly distant universes that constitute themselves as true "technologies and practices of self" as part of human search for itself: Kundalini Yoga, as taught by Yogi Bhajan, and the care of the self, as researched by Michel Foucault, mainly, in his studies of the 1980s. Being this research part of a professional master degree program, Kundalini Yoga workshops were conducted in a unit of the socio-educational system of Minas Gerais. In these experiments, it was possible to assess both practically and theoretically how the exercises of oneself intertwine themselves, so that the individuals can use them to requalify their relation with themselves. The methodology used was the philosophical cartography, based in the philosophy of Gilles Deleuze and Félix Guattari. Thus, the research refers itself to the creation of a rhizomatic map, which works in a non-hierarquical way. This means that there are no single closed centres of significations, for they are built through plans of consistency and plans of compositions where multiplicities are created. Therefore, one searches to outline different possibilities to think and practise education which can lead to effective transformation in the subjects. This can contribute to their own processes of singularization, that is, the ones which free themselves from the closed forms of subjectification, signification and organization.